The extraordinary deaths of Mrs. Kip : [large type] a novel - Brunsvold, Sara, 1979- (Center Point Large Print, 2024)
"Aidyn Kelley is talented, ambitious, and ready for a more serious assignment than the fluff pieces she's been getting as a cub reporter for the Kansas City Star. In her eagerness, she pushes too hard, earning herself the menial task of writing an obituary for an unremarkable woman who's just entered hospice care. But there's more to Clara Kip than meets the eye. The spirited septuagenarian may be dying, but she's not quite ready to cash it in yet. Never one to shy away from an assignment herself, she can see that God brought the young reporter into her life for a reason. And if it's a story Aidyn Kelley wants, that's just what Mrs. Kip will give her -- but she's going to have to work for it."--